Labdane Aldehyde Diterpenoids from Curcuma mangga Rhizome - Wartono, Muhammad Widyo; Aini, Qurotul; Suryanti, Venty; Firdaus, Maulidan; Rakhman Wibowo, Fajar; Dewi Marliyana, Soerya; Kusumaningsih, Triana; Suci Handayani, Desi (The Journal of Pure and Applied Chemistry Research, 2023)
Curcuma mangga val. (Zingiberaceae) is one of the plants that used as traditional medicine by Indonesian. Several studies have been reported on the content of compounds of C. mangga, but it is not yet known which compounds have medicinal properties. In this study, two labdane diterpenes were isolated from the extract of rhizome of C. mangga. Determination of the structure conducted by NMR (1H, 13C, HSQC and HMBC) that obtained two compounds, calcaratarin A (1) and labda-8(17),12-diene-15,16-dial (2). Both compounds have an aldehyde functional group. However, both compounds did not show antibacterial activity on Escherichia coli.